2006
DOI: 10.1016/j.jmwh.2006.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Providing Quality Care to the Sexual Assault Survivor: Education and Training for Medical Professionals

Abstract: Health care providers who perform sexual assault examinations can assist patients who report experiencing a sexual assault by increasing their knowledge and skills in sexual assault care, and serving as Sexual Assault Response Team (SART) coordinators, or as SART team members, in their communities. With little additional material, this training could be provided as a component of basic midwifery and/or advanced practice nursing education programs. This article reviews the essential steps and required training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…This focus of this review was limited to evaluation reports and peer-reviewed publications that (1) reported on systematic data collection and (2) examined SARTs’ effectiveness and/or challenges faced. Therefore, the following types of publications were excluded: theoretical discussions of the SART model (Ferguson, 2006; Girardin, 2005; Ledray, 1999; Taylor, 2002; Voekler, 1996; five studies), descriptive studies or discussion of individual SARTs (e.g., Botello, King, & Ratner, 2003; Dandino-Abbott, 1999; Fulginiti et al, 1996; Hatmaker, Pinholster, & Saye, 2002; Johnston, 2005; Peterson et al, 2009; Smith, Holmseth, MacGregor, & Letourneau, 1998; Zajac 2006, 2009; nine studies), and articles that sought to provide information about sexual assault to SARTs (Archambault & Faugno, 2001; Ledray, 2001b; Nakajima, 2005; three studies). Additionally, articles that described what a SART is, how it should be structured or function and/or its potential benefits, but did not report on systematic data collection or evaluation were excluded.…”
Section: Empirical Review Of Sarts’ Effectiveness and Challengesmentioning
confidence: 99%
“…This focus of this review was limited to evaluation reports and peer-reviewed publications that (1) reported on systematic data collection and (2) examined SARTs’ effectiveness and/or challenges faced. Therefore, the following types of publications were excluded: theoretical discussions of the SART model (Ferguson, 2006; Girardin, 2005; Ledray, 1999; Taylor, 2002; Voekler, 1996; five studies), descriptive studies or discussion of individual SARTs (e.g., Botello, King, & Ratner, 2003; Dandino-Abbott, 1999; Fulginiti et al, 1996; Hatmaker, Pinholster, & Saye, 2002; Johnston, 2005; Peterson et al, 2009; Smith, Holmseth, MacGregor, & Letourneau, 1998; Zajac 2006, 2009; nine studies), and articles that sought to provide information about sexual assault to SARTs (Archambault & Faugno, 2001; Ledray, 2001b; Nakajima, 2005; three studies). Additionally, articles that described what a SART is, how it should be structured or function and/or its potential benefits, but did not report on systematic data collection or evaluation were excluded.…”
Section: Empirical Review Of Sarts’ Effectiveness and Challengesmentioning
confidence: 99%
“…Family physicians should therefore develop increased awareness of sexual assault in their practices and should be adequately skilled to deal with such cases in practice. 31 Knowledge and skills in sexual assault care can be improved 32 and practitioners often require training in counselling and care of sexual assault victims. 33 Appropriate referral and adequate follow-up to prevent long-term sequelae such as depression and post-traumatic stress disorder are important.…”
Section: Literature Reviewmentioning
confidence: 99%
“…SANE training for the occupational health nurse and nurse practitioner can dramatically improve the quality of care, collection of evidence, and sub-AAOHN JOURNAL· VOL. 59, NO.1, 2011 sequent monitoring of victims of sexual assault (Canaff, 2009;Ferguson, 2006;Patel, Panchal, Piotrowski, & Patel, 2008). For the occupational health nurse or nurse practitioner, this training can result in properly caring for victims and effectively protecting employers from untoward damages due to assaults and inappropriate care in the community.…”
Section: Perpetrators and Victims Of Sexual Assaultmentioning
confidence: 99%